2017
DOI: 10.20471/acc.2017.56.01.11
|View full text |Cite
|
Sign up to set email alerts
|

High Tumor Stroma Proportion is a Worse Prognostic Factor in Colorectal Cancer

Abstract: SUMMARY -High stroma proportion appears to be a very important prognostic factor in esophageal and breast cancer. Previous researches have shown that it might have a similar eff ect on colorectal cancer. Th e aim of this study was to determine whether tumor stroma proportion infl uenced patient survival. Th is retrospective study included 236 patients with colorectal cancer having undergone surgery in 2006 and 2007 at Osijek University Hospital Center. Location with the highest stroma proportion at the site of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Refractory disease is defined as recurrence of disease during the course of platinum-based chemotherapy. There is evidence to support the hypothesis that stromatous components of malignant tumors stimulate growth and proliferation of malignant components of invasive tumors; higher stromal content, referred to as high tumor-stroma proportion , has been associated with worse prognosis in many epithelial cancers . We report the results of a prospective observational study examining tumor-stroma proportion as a predictive biomarker of chemoresistance in women diagnosed with ovarian cancer.…”
mentioning
confidence: 94%
“…Refractory disease is defined as recurrence of disease during the course of platinum-based chemotherapy. There is evidence to support the hypothesis that stromatous components of malignant tumors stimulate growth and proliferation of malignant components of invasive tumors; higher stromal content, referred to as high tumor-stroma proportion , has been associated with worse prognosis in many epithelial cancers . We report the results of a prospective observational study examining tumor-stroma proportion as a predictive biomarker of chemoresistance in women diagnosed with ovarian cancer.…”
mentioning
confidence: 94%
“…The number of patients in each study ranged from 65 to 1212. Among these 15 studies, 12 studies reported DFS as survival outcome ( 12 15 , 27 32 , 35 , 37 ), four reported CSS ( 14 , 33 , 34 , 36 ) and eight reported OS ( 13 , 15 , 27 , 28 , 31 , 32 , 35 , 37 ). Thirteen of the 15 articles had set the cutoff at 50% to divide patients into low-stroma and high-stroma groups ( 12 , 14 , 15 , 27 35 , 37 ), while one at 47% ( 36 ) and the other at 68% ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were of high quality, two studies by the same author contained the same patient group ( 37 , 38 ), thus the one with the larger sample size was included ( 37 ). Finally, four out of 12 studies did not report DFS analysis adjusted for confounding factors ( 15 , 28 , 30 , 32 ) [three out of eight OS studies ( 15 , 28 , 32 )], which indicated that there were some residual confounding factors in combined HR. Two studies did not report HRs for DFS directly ( 30 , 32 ) (while two for OS ( 30 , 32 )), we estimated HR from KM curve by the methods by Parmar et al ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not the case for OS. The latter result was somewhat surprising, since the majority of the TSR studies in colon cancer also reported the TSR as an independent prognosticator for this survival endpoint, either in pooled cohorts or subgroup analyses [17][18][19][20][27][28][29][30][31]. Nonetheless, demonstrating the prognostic power of the TSR with respect to CaDeath in a cohort of solely stage II disease is a valuable result, since this generally represents a group of individuals diagnosed via early detection screening programs and subsequently treated with local surgery.…”
Section: Discussionmentioning
confidence: 99%